2015
DOI: 10.1155/2015/486794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Single-Impact-Induced Cartilage Degeneration by Optical Coherence Tomography

Abstract: Posttraumatic osteoarthritis constitutes a major cause of disability in our increasingly elderly population. Unfortunately, current imaging modalities are too insensitive to detect early degenerative changes of this disease. Optical coherence tomography (OCT) is a promising nondestructive imaging technique that allows surface and subsurface imaging of cartilage, at near-histological resolution, and is principally applicable in vivo during arthroscopy. Thirty-four macroscopically normal human cartilage-bone sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Fissures proceed to increasing depths into the cartilage matrix following the arcade‐like architecture of the collagen network, that is, originally parallel to the articular surface and then transitioning into the radial orientation, until finally the fissures run along the calcified boundary and cartilage delamination occurs . The probability and severity of surface fissuring following trauma generally increases with higher impact energy, applied stress, stress rate, frequency of dynamic loading, loading duration, and a period of prolonged creep prior to overloading. From a certain impact threshold, in this case an impact energy of 0.25 J imposed on 5 mm diameter cartilage explants, it has even been observed that there was damage to the subchondral bone without macroscopic damage to the cartilage .…”
Section: In Vitro Studies; Short‐term Resultsmentioning
confidence: 99%
“…Fissures proceed to increasing depths into the cartilage matrix following the arcade‐like architecture of the collagen network, that is, originally parallel to the articular surface and then transitioning into the radial orientation, until finally the fissures run along the calcified boundary and cartilage delamination occurs . The probability and severity of surface fissuring following trauma generally increases with higher impact energy, applied stress, stress rate, frequency of dynamic loading, loading duration, and a period of prolonged creep prior to overloading. From a certain impact threshold, in this case an impact energy of 0.25 J imposed on 5 mm diameter cartilage explants, it has even been observed that there was damage to the subchondral bone without macroscopic damage to the cartilage .…”
Section: In Vitro Studies; Short‐term Resultsmentioning
confidence: 99%
“…Histology and analysis of proteoglycan content are standard methods in detecting early stages of post-traumatic AC degeneration in vitro [38,39]. These approaches showed no evidence of structural changes induced by the treatment, for instance, proteoglycan loss, collagen network degradation, and surface irregularity formation (i.e., erosion or fissuring).…”
Section: Delivery Future Studies Should Reveal the Dominant Mechanismentioning
confidence: 99%
“…Structural parameters obtained by the former included surface irregularity [optical irregularity index (OII)], tissue homogeneity [optical homogeneity index (OHI)], and signal penetration [optical attenuation index (OAI)] as described before. 12,14,17,36 Briefly, Savitzky-Golay filtering was applied to surface data matrices to obtain smoothed surface topographies. OII as a measure of surface integrity was defined as the standard deviation (SD) between the actual and the smoothed surface topography and calculated in absolute terms.…”
Section: Image Processing Of C-oct and Ps-oct Datamentioning
confidence: 99%